Textured one-dimensional all-inorganic lead-based halide perovskite polymer composite fibers, piezoelectric devices and their preparation methods

The textured one-dimensional all-inorganic lead-based halide perovskite polymer composite fiber was prepared by electrospinning technology, and the low-temperature shaping desolvent method and high-temperature multi-step phased hot pressing method were used to solve the existing piezoelectric material composite The random form leads to the problem of low piezoelectric performance, achieving the orientation arrangement of CsPbX3 inside polymer fibers and improving the piezoelectric performance.

CN116121900BActive Publication Date: 2025-02-21UNIV OF SCI & TECH BEIJING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310086616.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-02-21
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

The existing piezoelectric materials that are composited with CsPbX3 and polymers have random composite forms, resulting in the piezoelectric polarization electric fields canceling each other out, and the piezoelectric performance is low.

Method used

The textured one-dimensional all-inorganic lead-based halide perovskite polymer composite fiber was prepared by electrospinning technology, and the fibers were treated by low-temperature shaping and solvent removal method and high-temperature multi-step phased hot pressing method to form dense and orderly CsPbX3 nanometers Rod arrangement improves piezoelectric performance.

Benefits of technology

The orientation arrangement of CsPbX3 inside the polymer fiber is realized, reducing the mutual offset of the endogenous electric fields, and improving the piezoelectric properties and material stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116121900B_ABST
    Figure CN116121900B_ABST
Patent Text Reader

Abstract

The embodiment of the present invention discloses a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber, a piezoelectric device and a preparation method; the preparation method comprises: mixing a Cs source, a Pb source, a polymer, a ligand and an organic solution to prepare a precursor solution; wherein the Cs source is CsX, the Pb source is PbX2, wherein X is any one of Cl, Br and I; the polymer is any one of polyvinylidene fluoride, polystyrene and polymethyl methacrylate; the ligand is any combination of oleic acid and oleylamine; the organic solution is N,N-dimethyl Any combination of methylformamide and dimethyl sulfoxide; in the precursor solution, the mass ratio of Cs source and Pb source to the precursor solution is 4-20%, the mass ratio of oleylamine and oleic acid to the precursor solution is 3-12%, and the mass ratio of polymer to the precursor solution is 4-16%; the precursor solution is subjected to an electrospinning process to obtain a textured one-dimensional CsPbX3 / polymer composite fiber; wherein the electrospinning voltage is set to 10-20 kV, the temperature is set to 20-80°C, and the speed of the collecting drum is set to 100-1000 r / min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric materials, and in particular relates to a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber, a piezoelectric device and a preparation method thereof. Background Art

[0002] The piezoelectric effect refers to the phenomenon that when a piezoelectric material is subjected to an external force in a fixed direction, electric polarization is generated inside it, and charges of opposite signs are generated on two surfaces at the same time; the amount of charge generated by the piezoelectric material is proportional to the magnitude of the external force. Piezoelectric sensors based on the piezoelectric effect are widely used in the field of vibration detection.

[0003] All-inorganic lead-based halogen perovskite CsPbX 3 (X=Cl, Br or I) has attracted attention in the field of piezoelectric research due to its simple low-temperature wet preparation process, easy morphology control, and adjustable piezoelectric effect. 3 The water stability and oxygen stability of CsPbX are very poor, and it will be corroded and decomposed by water and oxygen in the air. 3 Composite piezoelectric materials can make CsPbX 3 The stability can be improved by isolating the water and oxygen in the air. On the other hand, the CsPbX 3 The piezoelectric properties of the material are improved by combining it with a polymer.

[0004] However, the CsPbX 3 The piezoelectric material composited with polymer has poor controllability due to the random composite form, which leads to the CsPbX 3 The generated piezoelectric polarization electric fields often cancel each other out, resulting in poor piezoelectric performance of the composite piezoelectric material. Summary of the invention

[0005] In view of this, on the one hand, some embodiments disclose a method for preparing a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber, the method comprising:

[0006] The Cs source, the Pb source, the polymer, the ligand and the organic solution are mixed to prepare a precursor solution; wherein the Cs source is CsX and the Pb source is PbX 2 , wherein X is any one of Cl, Br, and I; the polymer is any one of polyvinylidene fluoride, polystyrene, and polymethyl methacrylate; the ligand is any combination of oleic acid and oleylamine; the organic solution is any combination of N,N-dimethylformamide and dimethyl sulfoxide; in the precursor solution, the total mass ratio of the Cs source and the Pb source to the precursor solution is 4-20%, the total mass ratio of oleylamine and oleic acid to the precursor solution is 3-12%, and the mass ratio of the polymer to the precursor solution is 4-16%;

[0007] The precursor solution is subjected to an electrostatic spinning process to obtain a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber; wherein the electrostatic spinning voltage is set to 10-20 kV, the temperature is set to 20-80° C., and the collection drum speed is set to 100-1000 r / min.

[0008] Furthermore, in some embodiments of the method for preparing textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fibers, the molar ratio of the Cs source to the Pb source is 1:2 to 2:1.

[0009] In the preparation method of textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fibers disclosed in some embodiments, the volume ratio of oleylamine to oleic acid is 0:1 to 1:3.

[0010] Some embodiments disclose a method for preparing a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber, wherein the molecular weight of the polymer is 10 3 ~10 8 .

[0011] The preparation method of the textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber disclosed in some embodiments further includes:

[0012] The prepared textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fibers were prepared into textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber membranes using a low-temperature shaping and solvent removal method and a high-temperature multi-step phase-fixed hot pressing method.

[0013] Further, in some embodiments, the preparation method of the textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber disclosed in the embodiment includes the following steps:

[0014] The textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber is placed in a vacuum freeze dryer and frozen at -80 to -70°C and normal pressure for 10 to 60 minutes;

[0015] Then at -60℃ to -10℃ and 10 -2 ~10 2 Freeze-dry at Pa for 1 to 40 hours;

[0016] Then let it stand at room temperature and pressure for 1 to 20 hours.

[0017] The preparation method of the textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber disclosed in some embodiments, the high-temperature multi-step phased hot pressing method comprises:

[0018] The textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber treated by low-temperature setting and solvent removal is placed in a hot pressing furnace, heated to 80-110° C., with a pressure of 0-10N, and kept warm for 1-20 hours;

[0019] Cool down to 50-80℃, increase the pressure to 50-200N, and keep warm for 1-20 hours;

[0020] Raise the temperature to 80-110°C again, reduce the pressure to 0-10N, and keep warm for 1-10 hours;

[0021] The temperature is lowered to 50-80°C again, the pressure is increased to 50-200N, and the temperature is kept for 1-20 hours;

[0022] Finally, the temperature and pressure are reduced to room temperature and pressure to obtain a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite piezoelectric fiber film.

[0023] On the other hand, some embodiments disclose a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber membrane obtained by a preparation method of a textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber.

[0024] On the other hand, some embodiments disclose a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber piezoelectric device, including a textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber film.

[0025] Furthermore, some embodiments disclose a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber piezoelectric device, in which a textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber film is used as an active layer, both sides of the active layer are coated with a binder with a thickness of 20 to 50 μm, and aluminum foil is used as electrodes on both sides.

[0026] The method for preparing a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber disclosed in an embodiment of the present invention prepares a textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber, and then prepares a textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber membrane and a piezoelectric device using the fiber membrane as an active material; a one-dimensional CsPbX 3 Easier to realize one-dimensional CsPbX 3 Directed alignment inside polymer fibers and high aspect ratio one-dimensional CsPbX 3 It is beneficial to receive and transmit stress and improve energy conversion efficiency; highly ordered CsPbX in textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fibers 3 The arrangement of nanorods will relieve the internal clamping effect and reduce the mutual cancellation of the endogenous electric field. At the same time, the mutual contact between nanorods is also conducive to the piezoelectric charge from CsPbX 3The dense and smooth polymer encapsulation layer is more conducive to isolating water and oxygen in the air and preventing the internal CsPbX 3 It is corroded and decomposed, which improves the stability of the piezoelectric composite material and the stability of the piezoelectric device. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 CsPbI disclosed in some embodiments 3 Schematic diagram and SEM of nanorod / polymer composite fiber product structure Figure 1 ;

[0028] Figure 2 CsPbI disclosed in some embodiments 3 Schematic diagram and SEM of nanorod / polymer composite fiber product structure Figure 2 ;

[0029] Figure 3 CsPbI disclosed in some embodiments 3 Schematic diagram and SEM of nanorod / polymer composite fiber product structure Figure 3 ;

[0030] Figure 4 CsPbI disclosed in some embodiments 3 Schematic diagram and SEM of nanorod / polymer composite fiber product structure Figure 4 ;

[0031] Figure 5 CsPbI disclosed in some embodiments 3 Schematic diagram and SEM of nanorod / polymer composite fiber product structure Figure 5 ;

[0032] Figure 6 CsPbI disclosed in some embodiments 3 Schematic diagram and SEM of nanorod / polymer composite fiber product structure Figure 6 ;

[0033] Figure 7 CsPbI disclosed in some embodiments 3 Schematic diagram and SEM of nanorod / polymer composite fiber product structure Figure 7 ;

[0034] Figure 8 CsPbI disclosed in some embodiments 3 Schematic diagram, SEM and TEM images of the nanorod / polymer composite fiber product structure;

[0035] Fig. 9 Schematic diagram of the structure of piezoelectric devices disclosed in some embodiments;

[0036] Fig.10 Some embodiments disclose textured one-dimensional CsPbI 3 Voltage response diagram of nanorod / polymer composite fiber piezoelectric device under different pressures. DETAILED DESCRIPTION

[0037] The word "embodiment" used herein as an "exemplary" does not necessarily mean that any embodiment described is superior or better than other embodiments. Performance index tests in the embodiments of the present invention are performed using conventional test methods in the art unless otherwise specified. It should be understood that the terms described in the embodiments of the present invention are only used to describe specific implementation methods and are not intended to limit the contents disclosed in the embodiments of the present invention.

[0038] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the embodiments of the present invention belong; other experimental methods and technical means not specifically specified in the embodiments of the present invention refer to experimental methods and technical means commonly used by ordinary technicians in the field.

[0039] The terms "substantially" and "approximately" used herein are used to describe small fluctuations. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data represented or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values ​​clearly listed as the limits of the range, but also all independent values ​​or sub-ranges contained in the range. For example, the numerical range of "1-5%" should be interpreted as including not only the clearly listed values ​​of 1% to 5%, but also the independent values ​​and sub-ranges within the range shown. Therefore, independent values ​​such as 2%, 3.5% and 4% and sub-ranges such as 1%-3%, 2%-4% and 3%-5% are included in this numerical range. This principle also applies to the range of only one numerical value. In addition, such an interpretation applies regardless of the width of the range or the characteristics described.

[0040] In this document, including the claims, conjunctions such as "comprising", "including", "with", "having", "containing", "involving", "accommodating", etc. are understood to be open, that is, to mean "including but not limited to". Only the conjunctions "consisting of" and "composed of" are closed conjunctions. The texturing mentioned in this document generally refers to the directional arrangement of all-inorganic lead-based halogen perovskite nanorods inside and on the surface of polymer fibers to form a distribution of nanorods with consistent orientation. Textured one-dimensional CsPbX 3 / polymer fibers, or textured one-dimensional CsPbX 3The polymer fiber also refers to the textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber described in the embodiment of the present invention, which is a composite fiber obtained by directional distribution and arrangement of textured all-inorganic lead-based halogen perovskite nanorods inside and on the surface of the polymer fiber. The all-inorganic lead-based halogen perovskite can be expressed as CsPbX 3 .

[0041] In order to better illustrate the present invention, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the gist of the present invention.

[0042] Under the premise of no conflict, the technical features disclosed in the embodiments of the present invention may be arbitrarily combined, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present invention.

[0043] In some embodiments, some examples disclose a method for preparing a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber, the method comprising:

[0044] The Cs source, the Pb source, the polymer, the ligand and the organic solution are mixed to prepare a precursor solution; wherein the Cs source is CsX and the Pb source is PbX 2 , wherein X is any one of Cl, Br, and I; the polymer is any one of polyvinylidene fluoride (PVDF), polystyrene (PS), and polymethyl methacrylate (PMMA); the ligand is any combination of oleic acid (OA) and oleylamine (OAm), that is, it can usually be a combination of one or two of them; the organic solvent is any combination of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), that is, it can be a combination of any one or two of them; in the precursor solution, the total mass ratio of the Cs source and the Pb source to the precursor solution is 4-20%, the total mass ratio of oleylamine OAm and oleic acid OA to the precursor solution is 3-12%, and the mass ratio of the polymer to the precursor solution is 4-16%; usually, the Cs source refers to a substance including the Cs element, such as Cs halide CsX, and X is any one of the halogen elements Cl, Br, and I; usually, the Pb source refers to a substance including the Pb element, such as Pb halide CsX 2 , X is any one of the halogen elements Cl, Br, I; the all-inorganic lead-based halogen perovskite is CsPbX 3 ;

[0045] The precursor solution was electrospinned to obtain a textured one-dimensional CsPbX 3 / polymer fiber; wherein the electrospinning voltage is set to 10-20 kV, the temperature is set to 20-80° C., and the collection drum speed is set to 100-1000 r / min.

[0046] Generally, by adjusting the raw materials CsX and PbX 2 The ratio of the polymer, the type and molecular weight of the polymer, the type, ratio and concentration of the ligand, and the type, ratio and concentration of the organic solution can be adjusted to obtain CsPbX particles of different sizes and uniformities. 3 Nanoparticles and nanorods. A precursor solution can be prepared by mixing a Cs source, a Pb source, a polymer, a ligand and an organic solution.

[0047] In some embodiments, under electromagnetic stirring, DMF:DMSO is used as a solvent in a mass ratio of 0:1 to 1:0, and CsX:PbX is slowly added. 2 The molar ratio of Cs source and Pb source is 1:2 to 2:1, and after stirring, slowly add OAm:OA ligand with a volume ratio of 0:1 to 1:3, and then slowly add molecular weight 10 3 ~10 8 The mass ratio of solute to solution is controlled to be 10-30%, and the mixture is stirred evenly to obtain a precursor solution. The Cs source and the Pb source in the precursor solution interact to form a one-dimensional CsPbX 3 ; The mass ratio of the total mass of the Cs source and the Pb source to the precursor solution is 4 to 20%, the mass ratio of the total mass of OAm and OA to the precursor solution is 3 to 12%, and the mass ratio of the polymer to the precursor solution is 4 to 16%;

[0048] The precursor solution was transferred to a stainless steel needle tube, and the spinning voltage was adjusted to 10-20 kV, the temperature to 20-80 °C, and the collection tube speed to 100-1000 r / min to obtain a textured one-dimensional CsPbX 3 / polymer composite fibers.

[0049] Usually CsX is adsorbed on PbX 2 Nano-CsPbX 3 , so CsX and PbX 2 The ratio of OAm affects the type and morphology of the final product. OAm is a long-chain amine. 3 Provide attachment sites. Different ratios of OAm to OA provide different numbers of attachment sites. When there are few attachment sites, nano-CsPbX 3 The morphology is a nanorod with a large aspect ratio. As the number increases, the aspect ratio of the nanorods decreases, but the number increases. The addition of DMSO with higher coordination ability makes CsPbX 3 The crystallization is uniform, but DMSO has lower solubility and higher viscosity than DMF, which is not conducive to CsPbX 3 The crystal aspect ratio becomes larger, so the reasonable ratio and dosage of DMF and DMSO are conducive to the synthesis of uniform CsPbX with a large aspect ratio. 3Nanorods. Different polymer types and molecular weights also affect the viscosity of the mixed solution. The higher the viscosity, the better the CsPbX 3 Smaller and more uniform aspect ratio, lower viscosity CsPbX 3 The aspect ratio is large and non-uniform; the ratio of solute to solvent affects the CsPbX 3 The number of

[0050] In some embodiments, CsI and PbI 2 The molar ratio of is 0.6-0.8, the polymer is PVDF with a molecular weight of 600000-800000, the volume ratio of OAm and OA is 0-0.06, the mass ratio of DMSO and DMF is 0-15%, the mass ratio of solute to solution is 10-14%, wherein the mass ratio of Cs source and Pb source to precursor solution is 4-6%, the mass ratio of OAm and OA to precursor solution is 3-4%, and the mass ratio of polymer to precursor solution is 3-7%;

[0051] The precursor solution was electrospinned to obtain a textured one-dimensional CsPbX 3 / polymer fiber; wherein the electrospinning voltage is set to 10-12 kV, the temperature is set to 20-30° C., and the collection drum speed is set to 100-300 r / min;

[0052] Obtain CsPbI with a particle size of 10 to 25 nm 3 Nanoparticles, CsPbI 3 SEM image of nanorod / polymer composite fiber product Figure 1 As shown, CsPbI is generated on the surface and inside of the polymer fiber. 3 Nanoparticles. In this article, the solute includes a Cs source, a Pb source, and a polymer, and the solution is a precursor solution.

[0053] In some embodiments, CsI and PbI 2 When the molar ratio of 0.8 to 0.9, the polymer is PVDF with a molecular weight of 800000 to 1000000, the volume ratio of OAm to OA is 0.06 to 0.1, the mass ratio of DMSO to DMF is 15 to 25%, and the mass ratio of the solute to the solution is 14 to 19%, the mass ratio of the Cs source and the Pb source to the solution is 6 to 12%, the mass ratio of OAm and OA to the solution is 3 to 6%, and the mass ratio of the polymer to the solution is 5 to 10%;

[0054] The precursor solution was electrospinned to obtain a textured one-dimensional CsPbX 3 / polymer composite fiber; wherein the electrospinning voltage is set to 10-12 kV, the temperature is set to 20-30° C., and the collection drum speed is set to 100-300 r / min;

[0055] Obtain CsPbI with a length of 800 to 1000 nm 3 Nanorods; CsPbI 3 SEM image of nanorod / polymer composite fiber product Figure 2 As shown, CsPbI is generated on the surface and inside the polymer 3 Nanorods, length is 800~1000nm.

[0056] In some embodiments, CsI and PbI 2 When the molar ratio of 0.9 to 1.0, the polymer is PVDF with a molecular weight of 1,000,000 to 1,100,000, the volume ratio of OAm to OA is 0.1 to 0.12, the mass ratio of DMSO to DMF is 25 to 30%, and the mass ratio of the solute to the solution is 20 to 22%, the mass ratio of the Cs and Pb sources to the solution is 5 to 14%, the mass ratio of OAm and OA to the solution is 4 to 10%, and the mass ratio of the polymer to the solution is 3 to 13%;

[0057] The precursor solution was electrospinned to obtain a textured one-dimensional CsPbX 3 / polymer composite fiber; wherein the electrospinning voltage is set to 10-12 kV, the temperature is set to 20-30° C., and the collection drum speed is set to 100-300 r / min;

[0058] Obtain CsPbI with a length of 600-800 nm 3 Nanorods; CsPbI 3 SEM image of nanorod / polymer composite fiber product Figure 3 As shown, CsPbI is generated on the surface and inside the polymer 3 Nanorods, length is 600~800nm.

[0059] In some embodiments, CsI and PbI 2 When the molar ratio of Cs and Pb is 1.0-1.2, the polymer is PVDF with a molecular weight of 1,000,000-1,100,000, the volume ratio of OAm and OA is 0.12-0.14, the mass ratio of DMSO and DMF is 30-35%, and the mass ratio of the solute to the solution is 21-26%, the mass ratio of Cs and Pb sources to the solution is 7-17%, the mass ratio of OAm and OA to the solution is 4-12%, and the mass ratio of the polymer to the solution is 4-15%;

[0060] The precursor solution was electrospinned to obtain a textured one-dimensional CsPbX 3 / polymer composite fiber; wherein the electrospinning voltage is set to 10-12 kV, the temperature is set to 20-30° C., and the collection drum speed is set to 100-300 r / min;

[0061] Obtain CsPbI with a length of 200 to 500 nm 3 Nanorods; CsPbI 3 SEM image of nanorod / polymer composite fiber product Figure 4 As shown, CsPbI is generated on the surface and inside the polymer 3 Nanorods, length is 200~500nm.

[0062] Generally, during electrospinning, the smaller the fiber diameter, the stronger the electric field force. Due to the spatial confinement and electric field rearrangement inside the fiber, the smaller the angle between the nanorods and the fiber axis. The spinning voltage determines the magnitude of the electric field force. The higher the voltage, the stronger the pulling force on the fiber flying in the electric field, and the smaller the fiber diameter. At the same time, the electric field force has a greater impact on the CsPbX 3 The growth direction of the nanorods also plays a guiding role; the spinning temperature affects the viscosity of the precursor solution, which in turn affects the diameter of the fiber and the CsPbX 3 The difficulty of rearrangement of nanorod direction, the smaller the viscosity, the smaller the fiber diameter, CsPbX 3 The easier it is for the nanorods to rearrange their directions; the collection tube further pulls the fibers during the rotation collection process, while aligning the fibers with each other and the CsPbX 3 Nanorods are rearranged. In this application, one-dimensional CsPbX 3 The arrangement direction refers to CsPbX 3 The angle between the pointing direction of the nanorods and the fiber axis.

[0063] In some embodiments, CsPbI 3 / PVDF composite fiber preparation as an example;

[0064] CsI ​​and PbI 2 The molar ratio of is 1.1 to 1.0, the polymer is PVDF and has a molecular weight of 1000000 to 1100000, the volume ratio of OAm and OA is 0.12:1, the mass ratio of DMSO and DMF is 0.4:1, the mass ratio of solute to solution is 20%, wherein the mass ratio of Cs and Pb sources to the solution is 4%, the mass ratio of OAm and OA to the solution is 14 to 16%, and the mass ratio of polymer to the solution is 14 to 15%;

[0065] The spinning voltage was set to 15-16 kV, the spinning temperature was set to 30-40 °C, and the collection drum speed was set to 100-200 r / min to obtain CsPbI with a diameter of 1.5-1.8 μm. 3 / PVDF composite fiber, CsPbI 3 The angle between the nanorods and the PVDF fiber axis is 50-60°. Figure 5 As shown, CsPbI 3Nanorods are distributed on the surface and inside of PVDF fibers, CsPbI 3 The axial angle between the nanorods and the PVDF fibers is distributed between 50° and 60°.

[0066] In some embodiments, CsPbI 3 / PVDF composite fiber preparation as an example;

[0067] CsI ​​and PbI 2 The molar ratio of is 1.1 to 1.0, the polymer is PVDF and has a molecular weight of 1000000 to 1100000, the volume ratio of OAm and OA is 0.12:1, the mass ratio of DMSO and DMF is 0.4:1, the mass ratio of solute to solution is 20%, wherein the mass ratio of Cs and Pb sources to the solution is 4%, the mass ratio of OAm and OA to the solution is 14 to 16%, and the mass ratio of polymer to the solution is 14 to 15%;

[0068] The voltage was 16-17 kV, the spinning temperature was 35-40 °C, and the collection drum speed was 150-200 r / min to obtain CsPbI with a diameter of 1.3-1.6 μm. 3 / PVDF composite fiber, CsPbI 3 The angle between the nanorods and the PVDF fiber axis is 40 to 50°. Figure 6 As shown, CsPbI 3 Nanorods are distributed on the surface and inside of PVDF fibers, CsPbI 3 The axial angle between the nanorods and the PVDF fibers is distributed between 40° and 50°.

[0069] In some embodiments, CsPbI 3 / PVDF composite fiber preparation as an example;

[0070] CsI ​​and PbI 2 The molar ratio of is 1.1 to 1.0, the polymer is PVDF and has a molecular weight of 1000000 to 1100000, the volume ratio of OAm and OA is 0.12:1, the mass ratio of DMSO and DMF is 0.4:1, the mass ratio of solute to solution is 20%, wherein the mass ratio of Cs and Pb sources to the solution is 4%, the mass ratio of OAm and OA to the solution is 14 to 16%, and the mass ratio of polymer to the solution is 14 to 15%;

[0071] The voltage was 17-18 kV, the spinning temperature was 35-40 °C, and the collection drum speed was 200-250 r / min to obtain CsPbI with a diameter of 1-1.2 μm. 3 / PVDF composite fiber, CsPbI 3 The angle between the nanorods and the PVDF fiber axis is 25 to 35°. Figure 7As shown, CsPbI 3 Nanorods are distributed on the surface and inside of PVDF fibers, CsPbI 3 The axial angle between the nanorods and the PVDF fibers is distributed between 25° and 35°.

[0072] In some embodiments, CsPbI 3 / PVDF composite fiber preparation as an example;

[0073] CsI ​​and PbI 2 The molar ratio of is 1.1 to 1.0, the polymer is PVDF and has a molecular weight of 1000000 to 1100000, the volume ratio of OAm and OA is 0.12:1, the mass ratio of DMSO and DMF is 0.4:1, the mass ratio of solute to solution is 20%, wherein the mass ratio of Cs and Pb sources to the solution is 4%, the mass ratio of OAm and OA to the solution is 14 to 16%, and the mass ratio of polymer to the solution is 14 to 15%;

[0074] Using a voltage of 18-19 kV, a spinning temperature of 40-50 °C, and a collection drum speed of 250-300 r / min, CsPbI with a diameter of 0.8-1 μm was obtained. 3 / PVDF composite fiber, CsPbI 3 The angle between the nanorods and the PVDF fiber axis is 0 to 20°. Figure 8 As shown, CsPbI 3 Nanorods are distributed on the surface and inside of PVDF fibers, CsPbI 3 The axial angle between the nanorods and the PVDF fibers is distributed between 0 and 20°.

[0075] In some embodiments, the molar ratio of the Cs source to the Pb source is 1:2 to 2:1.

[0076] In some embodiments, the volume ratio of oleylamine to oleic acid is 0:1 to 1:3.

[0077] In some embodiments, the molecular weight of the polymer is 10 3 ~10 8 .

[0078] In some embodiments, the textured one-dimensional CsPbX 3 The method for preparing the polymer composite fiber also includes:

[0079] The textured one-dimensional CsPbX 3 / polymer composite fibers prepared as textured one-dimensional CsPbX 3 / polymer composite fiber membrane. Generally, the textured one-dimensional CsPbX3 / polymer composite fibers are tightly laminated together during the low-temperature shaping and solvent removal method and the high-temperature multi-step phase-fixing hot pressing method to form a film-like composite fiber membrane.

[0080] In some embodiments, the low temperature setting and solvent removal method comprises:

[0081] Textured 1D CsPbX 3 The polymer composite fiber is placed in a vacuum freeze dryer and frozen at -80 to -70°C and normal pressure for 10 to 60 minutes;

[0082] Then at -60°C to -10°C and 10 -2 ~10 2 Freeze-dry at Pa for 1 to 40 hours;

[0083] Then, the electrospinning process is allowed to stand for 1 to 20 hours at room temperature and pressure. 3 / Polymer composite fibers contain more solution, the fiber body is soft and easy to deform, and the evaporation of the residual solvent will cause the fiber to become porous, and it is impossible to form a fiber material with a dense surface and a round cross-section. During the low-temperature setting and solvent removal process, the textured one-dimensional CsPbX 3 The morphology of the CsPbX / polymer composite fiber was analyzed by slowly removing the remaining solvent in the fiber to obtain a textured one-dimensional CsPbX 3 / polymer composite fiber material.

[0084] In some embodiments, the high temperature multi-step phased hot pressing method comprises:

[0085] The textured one-dimensional CsPbX 3 / The polymer composite fiber is placed in a hot pressing furnace, heated to 80-110°C, with a pressure of 0-10N, and kept warm for 1-20 hours;

[0086] Cool down to 50-80℃, increase the pressure to 50-200N, and keep warm for 1-20 hours;

[0087] Raise the temperature to 80-110°C again, reduce the pressure to 0-10N, and keep warm for 1-10 hours;

[0088] The temperature is lowered to 50-80°C again, the pressure is increased to 50-200N, and the temperature is kept for 1-20 hours;

[0089] Finally, it was reduced to room temperature and pressure to obtain the textured one-dimensional CsPbX 3 / polymer composite piezoelectric fiber film. Generally, amorphous structural materials do not have piezoelectric properties. 3The polymers in the composite fibers are mostly amorphous phase structures. High temperature annealing can promote their crystallization and further improve the piezoelectric properties of the composite materials. At the same time, adding multiple steps of hot pressing during the annealing process can make the independent composite fibers tightly stacked together to form a film without destroying the morphology of the fiber itself, forming a textured one-dimensional CsPbX 3 / polymer composite fiber membrane has good piezoelectric properties and the textured one-dimensional CsPbX 3 / polymer composite piezoelectric fiber film. Textured one-dimensional CsPbX 3 / polymer composite piezoelectric fiber membrane thin film material is conducive to the further assembly of piezoelectric devices.

[0090] In some embodiments, the textured one-dimensional CsPbX 3 / polymer composite fiber membrane composed of textured one-dimensional CsPbX 3 / polymer composite fiber preparation method is obtained.

[0091] In some embodiments, the textured one-dimensional CsPbX 3 / polymer composite fiber piezoelectric devices, including textured one-dimensional CsPbX 3 / polymer composite fiber membrane.

[0092] In some embodiments, the textured one-dimensional CsPbX 3 Textured one-dimensional CsPbX / polymer composite fiber piezoelectric devices 3 The active layer is a polymer composite fiber membrane, both sides of the active layer are coated with a polydimethylsiloxane binder with a thickness of 20 to 50 μm, and aluminum foil is used as electrodes on both sides.

[0093] In some embodiments, first, a textured one-dimensional CsPbX 3 The nanorod polymer composite fiber film is cut into a suitable size as the active layer, and a layer of polydimethylsiloxane (PDMS) with a thickness of 20 to 50 μm is evenly applied on both sides as a binder. Aluminum foil is set on the binder on both sides as electrodes on both sides, and then placed in an oven for drying and curing to form a "sandwich" structure. Finally, polyimide tape is used for packaging to obtain a piezoelectric device with a sandwich structure. Fig. 9 As shown, the textured one-dimensional CsPbX 3The nanorod polymer composite fiber film is used as the active layer, located in the middle. A layer of polydimethylsiloxane (PDMS) with a thickness of 20 to 50 μm is evenly applied to the upper and lower surfaces of the active layer as a binder. Then, aluminum foil is placed outside the binder and bonded to it as the bottom electrode and the top electrode. After drying and curing, a piezoelectric device with a "sandwich" structure is formed. When the piezoelectric device is subjected to force, a piezoelectric potential is generated, and a voltage and current signal are output. The piezoelectric potential is positively correlated with the force, and its size can be judged by the voltage and current values, thus realizing the detection of force. Fig.10 As shown, the textured one-dimensional CsPbI 3 The voltage response diagram of the nanorod / polymer composite fiber piezoelectric device under different pressures. The response voltage is 56.7V when the pressure is 4.9N, the response voltage is 74.1V when the pressure is 5.9N, and the response voltage is 81.2V when the pressure is 6.9N, and the response voltage has good reproducibility.

[0094] Generally, the voltage and current generated by piezoelectric devices can power the device without the need for an external power supply, thus achieving the construction of an integrated device for force detection and self-driving.

[0095] The textured one-dimensional CsPbX disclosed in the embodiment of the present invention 3 The preparation method of / polymer composite fibers has produced textured one-dimensional CsPbX 3 / polymer composite fibers, and then textured one-dimensional CsPbX 3 / polymer composite fiber membrane and piezoelectric device using the fiber membrane as active material; Textured one-dimensional CsPbX 3 One-dimensional CsPbX / polymer composite fibers with high aspect ratio 3 Easier to realize one-dimensional CsPbX 3 Directed arrangement inside the fiber, and high aspect ratio one-dimensional CsPbX 3 It is beneficial to receive and transmit stress and improve energy conversion efficiency; texturing one-dimensional CsPbX 3 Highly ordered CsPbX / polymer composite fibers 3 The arrangement of nanorods will relieve the internal clamping effect and reduce the mutual cancellation of the endogenous electric field. At the same time, the mutual contact between nanorods is also conducive to the piezoelectric charge from CsPbX 3 The dense and smooth polymer encapsulation layer is more conducive to isolating water and oxygen in the air and preventing the internal CsPbX 3 It is corroded and decomposed, which improves the stability of the piezoelectric composite material and the stability of the piezoelectric device.

[0096] The technical solutions disclosed in the embodiments of the present invention and the technical details disclosed in the embodiments are merely illustrative of the inventive concept of the present invention and do not constitute a limitation on the technical solutions of the embodiments of the present invention. Any conventional changes, replacements or combinations of the technical details disclosed in the embodiments of the present invention have the same inventive concept as the present invention and are within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber membrane, characterized in that: include: A Cs source, a Pb source, a polymer, a ligand and an organic solution are mixed to prepare a precursor solution; wherein the Cs source is CsX, the Pb source is PbX2, and the molar ratio of the Cs source to the Pb source is 1:2 to 2:1; wherein X is any one of Cl, Br, and I; the polymer is any one of polyvinylidene fluoride, polystyrene, and polymethyl methacrylate, and the molecular weight of the polymer is 10 3 ~10 8 ; The ligand is a combination of oleic acid and oleylamine, and the volume ratio of the oleylamine to the oleic acid is 0.06:1 to 1:3; the organic solution is any one or a combination of N,N-dimethylformamide and dimethyl sulfoxide; in the precursor solution, the total mass ratio of the Cs source and the Pb source to the precursor solution is 4 to 20%, the total mass ratio of the oleylamine and the oleic acid to the precursor solution is 3 to 12%, and the mass ratio of the polymer to the precursor solution is 4 to 16%; The precursor solution is subjected to an electrostatic spinning process to obtain a one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber; wherein the electrostatic spinning voltage is set to 10-20 kV, the temperature is set to 20-80° C., and the collection drum speed is set to 100-1000 r / min; The one-dimensional all-inorganic lead-based halogen perovskite polymer fiber is prepared into a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber membrane by using a low-temperature shaping and solvent removal method and a high-temperature multi-step phase-fixed hot pressing method; Wherein, the low temperature setting and solvent removal method comprises: The one-dimensional all-inorganic lead-based halogen perovskite polymer fiber is placed in a vacuum freeze dryer and frozen at -80 to -70°C and normal pressure for 10 to 60 minutes; Then at -60℃ to -10℃ and 10 -2 ~10 2 Freeze-dry at Pa for 1 to 40 hours; Then let it stand for 1 to 20 hours at normal temperature and pressure; The high temperature multi-step phased hot pressing method comprises: The one-dimensional all-inorganic lead-based halogen perovskite polymer fiber treated by the low-temperature setting and solvent removal method is placed in a hot pressing furnace, heated to 80-110° C., with a pressure of 0-10N, and kept warm for 1-20 hours; Cool down to 50-80℃, increase the pressure to 50-200N, and keep warm for 1-20 hours; Raise the temperature to 80-110°C again, reduce the pressure to 0-10N, and keep warm for 1-10 hours; The temperature is lowered to 50-80°C again, the pressure is increased to 50-200N, and the temperature is kept for 1-20 hours; Finally, the temperature and pressure are reduced to room temperature and pressure to obtain a textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber membrane.

2. Textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber membrane, characterized in that: Obtained by the preparation method described in claim 1.

3. Textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber piezoelectric device, characterized in that: It comprises the textured one-dimensional all-inorganic lead-based halogen perovskite polymer fiber membrane as described in claim 2.

4. The textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber piezoelectric device according to claim 3, characterized in that: The textured one-dimensional all-inorganic lead-based halogen perovskite polymer composite fiber membrane is used as an active layer, both sides of the active layer are coated with a binder with a thickness of 20 to 50 μm, and aluminum foil is used as electrodes on both sides.

Citation Information

Patent Citations

  • Method for synthesizing CsPbX3 (X is Br, Cl and I) nanocrystal in situ and encapsulating in polymer fibers

    CN108360081A